Undergraduates Learn About Industrial–Organizational Psychology and Human Factors From an Informational Brochure. (January 2017) - Kottke, Janet L.; Shoenfelt, Elizabeth L.; Stone, Nancy J.
An informational brochure was created to assist students and faculty unfamiliar with the industrial–organizational (IO) and human factors (HF) disciplines. The brochure highlights the content of these two professions, presents advice for undergraduates to prepare for admission to IO and HF graduate programs, provides sources of IO and HF information, and suggests employability options in IO and HF. To determine if this brochure effectively informed students about these professions, students read either the IO and HF brochure or information about school psychology. Knowledge about IO and HF programs increased significantly after reading the IO and HF brochure. Suggestions for its distribution are offered.